COLLABORATIVE GOVERNANCE IN THE REPATRIATION SERVICE OF DISPLACED PERSONS BY THE SOCIAL SERVICE OF WOMEN'S EMPOWERMENT AND CHILD PROTECTION OF BALI PROVINCE - I Gede Krisna Santa Sedana; I.G.A.AG Dewi Sucitawathi Pinatih (RADJA PUBLIKA, 2026)
The government has the main responsibility to ensure social welfare, including abandoned services. As a migration location, Bali Province faces social problems because many displaced people need to be repatriated to their place of origin. The purpose of this study is to study the role of government cooperation in providing services for the repatriation of displaced persons by the Social Service for Women's Empowerment and Child Protection of Bali Province. This study uses a descriptive qualitative method and collects data through field observations, interviews, and documentation with important informants, including relevant agency officials and community members. Preliminary results show that the collaborative governance model involves cooperation between government agencies, NGOs, communities, and other non-governmental actors in formulating plans and implementing repatriation services. Building trust and accountability between parties and overcoming resource limitations requires effective cooperation. The study found that government cooperation is an effective method to improve the efficiency and quality of social services, especially for vulnerable groups such as displaced people. It is hoped that this research will contribute to the development of inclusive and sustainable social service policies in the future.